POTENTIAL ROLE OF CARICA PAPAYA AND THEIR ACTIVE CONSTITUENTS IN THE PREVENTION AND TREATMENT OF DISEASES - Rahmani, Arshad H; Aldebasi, Yousef H (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Natural products or products from the plant source show pivotal role in the diseases prevention and treatment since ancient. Numerous plants and their ingredients such as Nigella sativa, curcumin, olive and dates fruits have proven health promoting effects. In this vista, Papaya (C. Papaya family Caricaceae) is a medicinal plant that has been extensively used in traditional medicine due to their versatile approach in diseases treatment and prevention. The health-promoting activities of papaya and their constituents are recognized due to antioxidant activity. C. Papaya holds a range of valuable constituents such as vitamin, flavonoids and minerals in the different parts of plants and each constituent shows role in the disease management. Earlier reports have proven that C. papaya fruits and its ingredients shows role in health management via prevention of the pathogenesis of diseases. Its leaf juice also contains significant constituents, and they shows very effective role in the management of dengue fever with platelet increasing property. In this review, we aimed to evaluate the applications of papaya in cancer, diabetes, wound healing, malaria, dengue fever and other various disease prevention and treatment. Â 